The very quiet cricket - Carle, Eric. (New York : Philomel Books, 1990)
A very quiet cricket who wants to rub his wings together and make a sound as do so many other animals finally achieves his wish. The cricket$1 (Bs sound is reproduced at the end of the book.s
Keywords: Crickets -- Juvenile fiction; Sound effects books -- Specimens; Crickets -- Fiction; Animal sounds -- Fiction; Sound effects books; Toy and movable books